Should Indonesia Adopt Legal Representation in Civil Cases? - Elisabeth Sundari; Helidorus Chandera Halim; Ousu Mendy (Contrarius Indonesia, 2025)
Despite the recognised benefits of legal counsel and its increasing use in practice, the Indonesian legal framework does not sufficiently encourage legal representation in civil proceedings. This research examines the validity of Indonesia adopting and adapting mandatory legal representation. It encompasses a normative legal approach by examining and analysing qualitatively the Indonesian self-representation legal system and its secondary data of practices, the Netherland’s legal-representation framework comparatively, the theory of access to justice, as well as Posner’s law and economic analysis. This study shows that theoretically and practically, it is viable for Indonesia to adopt mandatory legal representation model in civil proceedings by establishing a compulsory legal framework to make it works effectively and promotes greater access to justice. However, based on a comparison to the Netherland’s framework, Indonesia needs to adapt it to the Indonesian context to overcome attorney fees challenge. First, by requiring legal representation only for complex civil cases. Second, by regulating legal fee agreements based on reasonableness, fairness, and transparency, and imposing strict legal sanctions on lawyers who refuse to provide pro bono legal assistance to litigants who cannot afford attorney fees. Third, strengthen the legal aid system by establishing a Legal Aids Board and providing adequate and sustainable funding. This research demonstrates that legal representation provides greater access to justice compared to self-litigation, in terms of ensuring fair, reasoned, and expedited judicial proceedings. In contrast, self-litigation primarily facilitates access to more affordable justice, as it eliminates the need to pay attorney fees.